FRACTURE RESISTANCE UNDER CYCLIC LOADING OF LITHIUM DISILICATE VONLAYS VERSUS ROSETTA VONLAYS RESTORING PREMOLARS (IN VITRO STUDY) - Ahmed, Mahmoud Showky Mohammed; Sami, Rasha Nabil; El Khodary, Noha Adel (Journal of medical and pharmaceutical sciences, 2021)
The aim of the study was to assess fracture resistance under cyclic loading of Rosetta®SM CAD vs. IPS e.max CAD (control) vonlays restoring maxillary premolars. According to the sample size calculation, a total of 20 samples will be selected and then divided into two equal groups; 10 sample each based on the material type: Group (A): Ten vonlays (n=10) manufactured from IPS e. max CAD blocks (control). Group ( B): Ten vonlays (n=10) manufactured from Rosetta®SM CAD blocks (intervention). A natural tooth presenting an upper first premolar was prepared in accordance with the ceramic onlay restorations preparation guidelines with an occlusal box with half of the bucco-lingual distance and a 2 mm depth from the cusp tip to pulpal floor, gingival seat with 1 mm depth from pulpal floor, occlusal reduction of 2 mm of the functional cusp with extending the preparation at the palatal surface by 2 mm in the cervical direction, occlusal reduction of 1.5 mm of non-functional cusp and 12º divergence angle. The preparation was then extended to the labial surface, with a 0.5 mm chamfer finish line. All line angles were finally rounded, and all margins were finished. For duplication of the natural tooth; the epoxy dies were constructed. Base and catalyst of the epoxy resin material were mixed as instructed by the manufacturer at a rate of 200r/min and then was poured into the silicon mould under vibration to eliminate any air voids, then was allowed to set completely following the manufacturer instructions for 24 hours, this procedure was repeated 20 times for creating 20 epoxy resin dies which replicating the prepared natural tooth. The die was then scanned by optical scanning using Medit i500 oral scanner. Milling of Vonlays was achieved using Sirona MCX5 milling machine using IPS e. max CAD blocks and Rosetta SM CAD blocks: 10 IPS e.max CAD blocks with block size C14 and 10 Rosetta®SM CAD blocks with block size C14 were used. Vonlays were then seated on their corresponding dies and cemented with dual cured self-adhesive resin cement (Variolink, Ivoclar Vivadent). Cementation procedures were performed by keeping each sample under a constant pressure of 5Kg using a custom designed cementation device for standardization the applied load during cementation process. All samples were mechanically aged (cyclic loading) to simulate 6 months of clinical use. Following that, all samples were subjected to fracture resistance testing under a compressive load to the center of their long axis using computer controlled universal testing machine with a load cell of 5 Kilo newton (K N) with a computer software used for data recording (Instron® Bluehill Lite Software). The mean values ± SDs values for e.max group were (502.39 ±102.89 N) with minimum value (338.16 N) and maximum value (721.29 N). The mean values ± SDs values. Rosetta group were (468.76 ± 67.54 N) with minimum value (367.11 N) and maximum value (648.48 N). Failure modes were determined under stereomicroscope and classified into repairable and catastrophic in both groups and showed that 60% of e.max group exhibited repairable failure while 40% of specimens showed catastrophic failure while in Rosetta group, 90% of the specimens exhibited repairable failure. Only 10% displayed catastrophic failure. Then a fractured part within each group was examined under scanning electron microscope (SEM) to reveal and compare their microstructure.